ANALISIS KESESUAIAN PENEMPATAN PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKANBARU - Sri Maryati Silaban; Arief Rifa'i (UIR Press, 2018)
This study aims to investigate the implementation of the Placement Officer at the Office of Population and Civil Registration Pekanabaru City and to know how the placement of civil servants in the Department of Population and Civil Registration Koata pekanbaru. Placement employee means an employee occupies a position, both structural and functional positions in an organization. Structural position is the position that indicates the duties, responsibilities, authority and a person's right of Civil Servants in order to lead an organizational unit of the state. With the staffing is done in the right position means indirectly own trust and responsibility to the civil servants concerned for the position. Although the deployment of staff in the Department of Population has been applied or implemented optilam, but based on the data in views, there are things or irregularities ditemuakan in the implementation of the deployment of staff, namely that the staffing they do not see on the side of working life / work experience , education and classes that employees have. Because they do not base it on the side of working life / work experience to occupy a structural position and still there are employees who do not disenioritaskan tenure, and employees who have a high class they occupy as a staff. Therefore, to conduct this study the authors provide data / information related to the issue being investigated. The types and sources of data used are primary data and secondary data. Primary data is data that is processed from the questionnaire sdangkan secondary data include data on the implementation of the staffing and organizational structure of government in the Department of Population and Civil Registration Pekanbaru.Populasi City and samples in this study were 20 people and a sample of 20 people, where there are Head Office, Subbid procurement, placement and employee pension, Secretary, Head. Public and Civil Service, Head of Division, and Head of the section. Descriptive data were analyzed quantitatively. Mechanical sampling using sensus.Teknik used data collection were questionnaires, interviews, observation and documentation. Technical analysis of the data used is quantitative descriptive data anlisis quantitative research data is data collection for which data are numbers - statistics can in quantification. The data in the form of variables - variables and operationalization with a particular size scale scale eg nominal, ordinal, interval and ratio.